Bimbingan Klasikal Berbasis Mindfulness dan Dampaknya terhadap Motivasi Belajar Siswa Sekolah Menengah Atas - Maykam, Mawaddatul; Yusuf, Ahmad; Nurhamzah, Wahyu (Universitas Muhammadiyah Enrekang, 2025)
This study aims to examine the effect of mindfulness-based classical guidance on improving students’ learning motivation at SMA Negeri 7 Sinjai. The scope of the research focuses on grade XI students who exhibited low levels of learning motivation, by analyzing changes in motivation after receiving the intervention of mindfulness-based classical guidance services. The study employed a quantitative approach using an experimental method with a Non-Equivalent Control Group Design. The research sample consisted of 60 students selected purposively, and then divided into two groups: 30 students as the experimental group who received mindfulness-based classical guidance services, and 30 students as the control group without treatment. The research instrument was a learning motivation questionnaire using a Likert scale that had been tested for validity and reliability. The findings reveal a significant difference between the experimental and control groups. The distribution of learning motivation scores in the experimental group showed a substantial improvement, shifting from low and medium categories to high and very high categories. In contrast, the control group remained predominantly in the low and medium categories. An independent t-test indicated a significance value of 0.010 (< 0.05), confirming that mindfulness-based classical guidance interventions positively influence the enhancement of students’ learning motivation. In conclusion, the implementation of mindfulness-based classical guidance is proven effective in helping students improve focus, emotional regulation, self-awareness, and the ability to manage academic stress. Therefore, this approach can serve as an alternative strategy for guidance and counseling services to foster students’ learning motivation while providing practical contributions to the development of counseling practices in secondary schools.